2022
DOI: 10.1007/s40145-022-0586-2
|View full text |Cite
|
Sign up to set email alerts
|

Modification of YSZ fiber composites by Al2TiO5 fibers for high thermal shock resistance

Abstract: Yttria-stabilized zirconia (YSZ) fiber composites are highly efficient thermal insulating materials; however, the poor thermal shock resistance limits their versatile applications. In the present study, YSZ fiber was mixed directly with Al2TiO5 fiber, which had an extremely low thermal expansion coefficient, to prepare YSZ−Al2TiO5 (ZAT) fiber composites by compression molding and heat treatment. The minimum thermal expansion coefficient of the prepared ZAT fiber composites was measured to be 7.74×10−6 K−1, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…The results further indicated that SiZrNOC-7 NFMs have excellent high-temperature thermal insulation performance. Moreover, we compared the λ at 1000 ℃ of SiZrNOC-7 NFMs with other ceramic fiber membranes, such as ZrO 2 [6,26], mullite [7,27], carbon [28,29], MgSiO 3 [30], and SiZrOC [13] (Fig. 6(d)).…”
Section: Thermal Insulation Performancementioning
confidence: 99%
See 2 more Smart Citations
“…The results further indicated that SiZrNOC-7 NFMs have excellent high-temperature thermal insulation performance. Moreover, we compared the λ at 1000 ℃ of SiZrNOC-7 NFMs with other ceramic fiber membranes, such as ZrO 2 [6,26], mullite [7,27], carbon [28,29], MgSiO 3 [30], and SiZrOC [13] (Fig. 6(d)).…”
Section: Thermal Insulation Performancementioning
confidence: 99%
“…Especially, the thermal insulating materials working under extreme conditions, such as long-term high-temperature (≥ 1000 ℃) exposure and rapid thermal shocking, are urgently required in the fields of aerospace, nuclear power engineering, and industry furnace [1,2]. In the past few decades, the ceramic fibers (such as SiO 2 , ZrO 2 , Al 2 O 3 , and mullite) are the most developed and widely investigated hightemperature thermal insulating materials due to their low density, low solid thermal conductivity, and excellent fire and high-temperature resistance [1][2][3][4][5][6]. They can be used as either flexible thermal insulators or reinforcements of aerogel thermal insulators, which are both urgently needed in high-temperature thermal insulation fields [7][8][9].…”
Section: Introduction mentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of the unique three-dimensional fiber-connection networks, porous fibrous ceramics have a series of outstanding physical and chemical properties, such as high porosity, low thermal conductivity, and excellent high temperature-resistance properties. Recently, porous fibrous ceramics have been widely applied in various fields, such as energy conservation, recycling industry, and high-temperature thermal insulation. With the rapid development of technology and industry, higher requirements are put forward for porous fibrous ceramics with comprehensive performances, including low density, low thermal conductivity, and high mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the presence of organic ligands in the precursors, their decomposition during heat treatment tends to destroy the structure of the fibers, which is the main reason for the difficulty in obtaining high-performance continuous fibers. Although researchers have prepared a series of high-temperature-resistant oxide submicron fibers and continuous fibers such as Al 2 O 3 [22], ZrO 2 [23][24][25][26], HfO 2 [27], TiO 2 [28], Y 2 O 3 [29], SiO 2 [30,31], mullite [32,33], Al 2 TiO 5 [34], and Y 3 Al 5 O 12 [35] through the precursor method. Due to the large differences in the structure of ligands, metal element types, and fiber diameters, the heat treatment methods of various fibers are also very different.…”
Section: Introduction mentioning
confidence: 99%